2003
DOI: 10.1007/s00277-002-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applicability of the new EORTC/MSG classification for invasive pulmonary aspergillosis in patients with hematological malignancies and autopsy-confirmed invasive aspergillosis

Abstract: Diagnosis of invasive pulmonary aspergillosis (IPA) is often difficult. Recently, the European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) has proposed new criteria for the classification of invasive fungal infections. We have studied the clinical applicability of this classification in 22 patients with hematological malignancies who had IPA at autopsy. While alive, according to the EORTC/MSG criteria, only 2 patients were classified as having proven IPA, 6 as probable, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 7 publications
3
62
0
1
Order By: Relevance
“…In addition, because the patients had unique host factors, one should be careful when applying these findings to other patient populations with different risk factors. Subira et al 19 reported similar findings, namely that only 36% of autopsy-proven IPA cases in their study were diagnosed premortem using the EORTC/MSG criteria. Hence, the problem with the EORTC/MSG criteria is that they are not evidence-based or autopsy-proven methods of diagnosing invasive fungal infections that have been established through well -designed multivariate analysis studies.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, because the patients had unique host factors, one should be careful when applying these findings to other patient populations with different risk factors. Subira et al 19 reported similar findings, namely that only 36% of autopsy-proven IPA cases in their study were diagnosed premortem using the EORTC/MSG criteria. Hence, the problem with the EORTC/MSG criteria is that they are not evidence-based or autopsy-proven methods of diagnosing invasive fungal infections that have been established through well -designed multivariate analysis studies.…”
Section: Discussionsupporting
confidence: 65%
“…antifungal therapy relied in all cases on an individualized clinical judgement (for example, patient general condition, signs and symptoms, test results and treatment compliance), rather than on the fulfilment of EORTC IFD criteria, which were not developed to fit this daily clinical practice purpose. [20][21][22] Persistent fever was considered too unspecific to trigger a change in antifungal treatment on its own. 23 Neither itraconazole nor posaconazole drug level monitoring were available during this study to guide clinical decisions.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Fungal infections were classified as 'proven', 'probable' or 'possible' according to the European Organisation for Research and Treatment of Cancer (EORTC) criteria (Subira et al, 2003). Cytomegalovirus (CMV) antigenin was calculated by determining serum pp65 antigen at least three times weekly.…”
Section: Assessment Of Toxicity Infections and Cgvhdmentioning
confidence: 99%